The Identification of New Bioactive Molecules Selectively Targeting the Human Cancer Stem Cell Epigenetic Signature - Bergin, Christopher (Université d'Ottawa / University of Ottawa, 2023)
Colorectal cancer (CRC) is one of the most prevalent cancers worldwide and is recognized as the second leading cause of cancer-related deaths in North America. CRC follows a hierarchal tumor organization, the root being a small population of self-renewing and highly tumorigenic colon cancer stem cells (CSC). There is an epigenetic signature that exists within these colon CSCs contributing to their maintenance and dynamic plasticity. A key hallmark of this colon CSC epigenetic signature is the Histone-3 Lysine-9 di-methylation (H3K9me2) histone mark which is overrepresented in many types of cancer. Pharmacological modulation of this epigenetic signature (i.e through H3K9me2 modulation) serves as a novel way to selectively target and eliminate human CSCs while sparing normal progenitor cells. Direct inhibitors of key methyltransferases such as G9a, have been identified to have high specificity, however none of these inhibitors have shown success during early stages of clinical trials, leaving us to question the clinical relevance. My research has shown that the overexpression of histone methyltransferase G9a in colon cancer serves as a risk factor for patients and is associated with shorter-relapse free survival. G9a activity has been shown to be essential for the maintenance of embryonic-like transcriptional signature which promotes self-renewal, tumorigenicity and an undifferentiated state. This work provides insights into the role of G9a as a driver of a cancer stem cell phenotype. To combat the toxicity and issues associated with targeting the catalytic activity of G9a, I utilized a phenotypic screening pipeline consisting of thousands of clinically-approved compounds, and identified CSC-bioactive epigenetic inhibitors showing promise in CSC-like models. RNA-seq profiling, dose response treatments and molecular techniques were used to confirm the selectivity of these candidates to colon-CSC like cells with minimal impact on normal progenitors. The lead candidate compound, vanoxerine (VXN) restricts organoid-initiating capacity of patient derived colon CSCs in serial 3D organoid formation assays that I developed throughout my research project. Using two murine syngeneic models resembling microsatellite instability and stability in CRC, I found this compound to be successful in decreasing primary tumor volumes compared to vehicle control mice, through epigenetic reprogramming and infiltration of immune cells. Drug treated tumors that were harvested, dissociated and re-injected into secondary mice showed diminished tumor initiating capacity compared to vehicle controls. Furthermore, the target of vanoxerine, SLC6A3, was investigated and the expression pattern characterized revealed a new potential biomarker for colon cancer stem cells. This SLC6A3-G9a axis discovered for the first time in colon cancer and serves as a novel and important pathway to block H3K9me2 deposition in CRC, rewiring the CSC epigenome and suppressing neoplastic self-renewal and tumor-initiating functions. Together, the identified repurposed compound selectively targets and modulates the epigenetic signature of CSCs which diminishes the tumor initiating function of these cells. This hints at an interesting interaction between CRC stemness and tumor immunology, a promising future therapeutic avenue.
Keywords: Colorectal Cancer; Cancer Stem Cells; Epigenetics; Drug Repurposing; Drug Screening; Organoids; Cancer